Incorporação de óxido de cério em vidros teluritos para o desenvolvimento de dispositivos ópticos - Silva, Edenilson da (2019)
The effects of Cerium incorporation in a Zinc-Tellurite glass containing Sodium and Lanthanum (TZNL) has been investigated. Samples were produced under air atmosphere and thermal, structural and spectroscopic data was acquired. The doped samples exhibited a reddish luminescence under 405 nm excitation, though its origin is attributed to Te4+ions. Under 450 nm pumping we observed a broadband from 600-750nm in all samples, including the matrix. X-ray diffractograms (XRD) andFourier transform infrared spectroscopy (FT-IR) analysis confirmed that Cerium is inducing structural changes in the glass and even though Ce3+were not detected directly, its presence is not discarded because the excitation of the Te4+band observed in the TZNL glass is different from the reported in the literature in such way that Ce3+may playing some role. An additional excitation/emission study is needed in order to clarify the question.